Reativação da retocolite ulcerativa com o uso de droga anti-inflamatória não esteróide: relato de caso e revisão da literatura - Dichi, I. [UNESP]; Dichi, J. B. [UNESP]; Frenhane, P. [UNESP]; Rodrigues, M. A. [UNESP]; Burini, Roberto Carlos [UNESP]; Victória, C. R. [UNESP] (My University, 1995)
The case of a patient with ulcerative colitis and isolated sacro-ileitis is presented. She suffered reactivation of the intestinal disease with diclofenac. The patient was allergic to sulfasalazine and was using fish oil fatty acid. The possible mechanisms of reactivation of the inflammatory bowel disease with non-steroidal anti-inflammatory drugs are discussed. It is suggested when necessary the utilization of non-steroidal anti-inflammatory drugs that inhibits the lipoxygenase in these patients.
Reactivation of ulcerative rectocolitis with the use of non-steroidal anti-inflammatory drugs: report of a case and review of the literature
Keywords: diclofenac; nonsteroid antiinflammatory agent; unsaturated fatty acid; case report; female; human; ileitis; middle aged; review; ulcerative colitis; Anti-Inflammatory Agents, Non-Steroidal; Colitis, Ulcerative; Diclofenac; Fatty Acids, Unsaturated; Female; Humans; Ileitis; Middle Aged